The ethics of personalising risk using big data in the pricing and underwriting of life insurance - Groenewald, Andries (My University, 2021)
This research report investigates whether the use of big data to personalise risk in the pricing and underwriting of life insurance undermines the delicate balance of factors that allow the industry to be morally justified. The practice of risk classification in the pricing and underwriting of life insurance can be regarded as unethical given the resemblance to discrimination. A consequentialist justification for the practice is presented. It is then investigated whether the use of new factors derived from the analysis of big data invalidates the justification. It is found that such factors can be used subject to certain conditions being met
A research report submitted n partial fulfilment of the requirements for the degree of Master of Arts in Applied Ethics for Professionals to the Faculty of Humanities, University of the Witwatersrand, 2021